Public Policy Strategies to Enhance Creative Tourism Competitiveness in Lanzhou: Insights from Porter's Diamond Model (Lex localis - Journal of Local Self-Government, 2025)
Lanzhou is an important node along the "Silk Road Tour", with deep historical and cultural heritage and rich creative tourism resources, but its tourism development is unsatisfactory. Based on Porter's diamond model, this paper divides Lanzhou's creative tourism competitiveness into tourism industry, environment and economy. The development and dynamic evolution level of tourism competitiveness in the region is analyzed by using the kernel density estimation method, and the global spatial autocorrelation is used to explore the degree of association and spatial distribution pattern of tourism competitiveness in the region. Identify the hot and cold zones of creative tourism competitiveness development in Lanzhou City through Getis Ord index and standard deviation ellipse. The triangular model is used to evaluate the coordination status and change trend of Lanzhou's creative tourism industry, environment and economy, and to measure the health status of the whole region's tourism system. Through the research on the level of creative tourism competitiveness in Lanzhou City, the spatio-temporal evolution law, and the spatio-temporal effects of the influencing factors from 2014 to 2023, the internal mechanism and power mechanism of tourism competitiveness enhancement are elaborated. The results show that the overall level of creative tourism competitiveness in Lanzhou City is on the rise, evolving from bipolarization to multipolarization, with the gradient effect increasing and the regional gap gradually narrowing. Meanwhile, the global Moran's I of all regions in Lanzhou City is positive, and the local Moran's I index shows a decreasing trend in general, from 0.168 in 2014 to 0.107 in 2023, which indicates that the spatial relationship of the competitiveness of creative tourism in Lanzhou City is relatively close, and there is a significant spatial positive correlation. Geographically, it presents significant spatial positive aggregation characteristics, and can play a certain radiation-driven role.